Cause Related Marketing An Effective Use Of A Promising Marketing Tool - Lohia, Sonia (International Journal of Scientific Research and Management (IJSRM), 2017)
This study elucidates how cause related marketing is an innovative and potentially powerful tool to improve the lives and well-being of individuals thereby creating an environment that supports social objectives, reorient social services to be customer driven ,develop social capital and lead to improved public policies .It is simply a marketing with a worthy cause that uses both business and charity (good causes) and helps to benefit both. This paper identifies some of the influential work in CRM area, highlighting the concept, meaning and different dimensions of CRM. The paper also outlines the evaluation of CRM program and recommendations and suggestions drawn there from.